Research on Green Production Factors by OFDI Along the Belt and Road Initiative (Contemporary Mathematics, 2024)
To analyze the role of the Belt and Road Initiative in China’s OFDI by applying a double-difference model. To determine the accuracy of the model, using the skewed distribution matching method, and to determine the effect of OFDI in China’s coastal areas through practical tests. This paper adopts the DEA’s SBM model to study China’s green total factor productivity in 31 provinces; it evaluates China’s outward foreign direct investment (OFDI) through the use of three key indicators, including the currencies of the inflow countries, the currencies of the inward total, and exchange rate changes. The research in this paper considers various factors under the Belt and Road Initiative, including OFDI flows, reserves, and net flows. After an in-depth study, it is found that the Belt and Road policy significantly improves the mobility and sustainability of OFDI in the regions along the Belt and Road. This study may provide new perspectives for understanding the economic and social development patterns of provinces along the Belt and Road Initiative. Dissecting the complexity of regional development through the use of a "double split model" helps to recognize the different impacts of international projects on the local economy, and uniquely accounts for both spatial (geographic) and temporal (over time) variations in development, providing a robust framework for similar studies in other contexts.
Keywords: economic construction; Belt and Road; green total factor productivity; outward foreign direct investment; double difference modelling